Connecting the dots: Secondary science teacher candidates' uptake of the core practice of facilitating sensemaking discussions from teacher education experiences. (April 2019) - Kloser, Matthew; Wilsey, Matthew; Madkins, Tia C.; Windschitl, Mark
Highlights: Rehearsals of teaching practice function as a bridge from methods to the classroom. Organizational tools help increase the visual representations during discussions. Elements of framing and closing discussions are taken up less to the classroom. Talk moves are taken up extensively in rehearsals and the classroom. Explicit representations of practice are most often taken up by novice teachers.